Enhancing Accuracy in Food Security Services: Challenges and Technological Solutions - Yakob Thomas Ngobut; Normawati Normawati; St. K. Ohoiwutun (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2025)
This research is significant because the accuracy of public services in the field of food security directly influences food availability and community welfare in Maluku Province. The study aims to examine the precision and effectiveness of public services delivered by the Maluku Provincial Food Security Agency in implementing market operations. A descriptive qualitative method was employed, utilizing interviews, observations, and document analysis as data collection techniques. The findings indicate that, despite facing challenges such as limited technological infrastructure and coordination barriers, the agency has demonstrated effectiveness in executing market operations. The study concludes that enhancing the use of technology and strengthening collaboration among stakeholders are crucial steps toward improving the accuracy and reliability of public services in the region's food security sector.